Arkansas Music Curriculum Framework 1997 - Arkansas State Dept. of Education, Little Rock.; Arkansas State Dept. of Education, Little Rock. ([Washington D.C.] : Distributed by ERIC Clearinghouse, 1997)
This framework for music contains four instructional strands. Each strand has content standards and cumulative student learning expectations for grades K-4, grades 5-8, and grades 9-12. The strands are: (1) "Create and Perform," in which students will demonstrate musical competency through creating and performing; (2) "Listen Perceive, and Analyze," in which students will demonstrate a response to diverse styles of music through listening, perceiving, and analyzing; (3) "Cultural and Historical Contexts," in which students will develop an understanding of the relationships of music to history and culture; and (4) "Connect and Apply," in which students will demonstrate an understanding of the relationships between music and the other arts, and disciplines outside the arts, and an understanding of the relationships of music to career and life-long applications. (BT)
ERIC Note: For other Arkansas Curriculum Frameworks, see SO 030 602-605.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Standards; Elementary Secondary Education; Music; Music Activities; Music Education; Public Schools; State Curriculum Guides; State Standards; Student Educational Objectives; Arkansas; Guides, Non-Classroom.